The Relationship of One Leg Standing Duration to GMFM Scores and to Stance Phase of Walking in Children with Hemiplegic Cerebral Palsy - UZUNOĞLU, GAMZE ERTÜRK; AKALAN, NAZİF EKİN; EVRENDİLEK, HALENUR; YILMAZ, GÜLŞAH KARACA; Bilgili, Fuat (Taylor & Francis, 2021)
Background: Lack of stability during stance negatively impacts gait and motor function for children with unilateral cerebral palsy. Improving stability and balance are the focus for gait rehabilitation). The One-Leg-Standing-Test may give valuable information about motor function and stability of stance for patients with unilateral cerebral palsy. Objective: This study aimed to investigate the relationship between the One-Leg-Standing-Test and the gross-motor-function-measurement and single-limb support time. Methods: The study included 18 patients with unilateral cerebral palsy (age 11.08 [SD 2.84] years old). The One-Leg-Standing-Test and pedobarographic evaluation were performed. Sections D and E of the gross-motor-function-measurement were assessed, and in pedobarographic evaluation, the single-limb support time (the total duration of mid-stance and terminal-stance during walking) was calculated to describe stability during stance. Results: For patients, the One-Leg-Standing-Test scores and single-limb support time values were lower on the affected side than on the unaffected side. The One-Leg-Standing-Test was correlated with single-limb support time (p = .02, r = 0.60) and section E (p < .01, r = 0.59) values. The One-Leg-Standing-Test was also correlated to total stance phase and section D. Conclusion: The One-Leg-Standing-Test gives valuable information about gross-motor-function but cannot be substituted for motor function tests. The single-limb support time value may be used to describe stability in stance during walking.
Keywords: Cerebral Palsy; Gait; Gross Motor Function Measurement; Stability; Foot Pressure